PENGEMBANGAN MEDIA BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR - Sitorus, Michael; Misbah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low motivation of students to learn Indonesian, schools focus more on textbooks. This research aims to develop a picture storybook learning media to increase students' learning motivation in Indonesian Language subjects. This research uses the Research and Development (R&D) method using the ADDIE model which consists of five stages, namely analysis, design, development, implementation and evaluation. The results of the study show that the media of illustrated storybooks is declared "very valid" to be tested, as evidenced by the results of linguist assessments with a percentage of 94%, media expert assessments with a percentage of 94%, and material expert assessments with a percentage of 92%. The teacher's response and students' response to the serial image media were obtained as a percentage of 92% and 90% could be declared "very good" as an Indonesian Language learning medium to increase students' learning motivation. The media of illustrated storybooks was declared effective in increasing student learning motivation as evidenced by the results of the assessment of student learning motivation observation sheets which obtained a result of 91% with the criterion of "very effective". It can be concluded that the media of picture storybooks as a medium for learning Indonesian Language can increase the learning motivation of grade IV students of SDN Wanajaya 05.